Pension De-risking - Paul M. Secunda; Brendan S. Maher (Washington University Law Review, 2016)
The United States is facing a retirement crisis, in significant part because defined benefit pension plans have been replaced by defined contribution retirement plans that, whatever their theoretical merit, have left significant numbers of workers unprepared for retirement. A troubling example of the continuing movement away from defined benefit plans is a new phenomenon euphemistically called “pension de-risking.” Recent years have been marked by high-profile companies engaging in various actions designed to reduce the company’s exposure to pension funding risk (hence the term “pension de-risking”). Some de-risking strategies convert a federally-guaranteed pension into a riskier private annuity. Other approaches convert the pension into cash for the beneficiary, which may be insufficient to provide lasting retirement income. These strategies have raised many concerns that participants are being disadvantaged and that pension de-risking is undermining the statutory purpose of ERISA. Regulators are only beginning to consider ways to appropriately police pension de-risking behavior. We propose that the government should take an aggressive stance in regulating such conduct. Participants as a class should not be made worse off by a pension de-risking transaction, and the relevant de-risking rules should so reflect. More specifically, regulators should: (1) encourage desirable forms of de-risking by establishing regulatory safe harbors; (2) require a battery of procedural safeguards for annuitization transactions; (3) require improved disclosures for cash buyouts; and (4) limit cash buyouts when beneficiaries are not likely to meaningfully understand the potentially adverse consequences of trading a pension for cash.
Keywords: Labor Law; Employment Law; Pension de-risking; Pensions; ERISA